Regression analysis unified concepts, practical applications, and computer implementation - Bowerman, Bruce L.; O'Connell, Richard T.; Murphree, Emily S. (Business Expert Press, 2015)
Preface -- 1. An introduction to regression analysis -- 2. Simple and multiple regression: an integrated approach -- 3. More advanced regression models -- 4. Model building and model diagnostics -- Appendix A. Statistical tables -- References -- Index
Part of: 2014 digital library
Includes bibliographical references (page [261]) and index
Keywords: Regression analysis